Urban "Skiluaf technik" Kožichovice - Hromada, Matěj (Vysoké učení technické v Brně. Fakulta architektury, 2025)
Budova bývalé školy v Kožichovicích, založená roku 1789, prošla řadou proměn a nyní čeká na adaptaci. Urbanistický návrh otevírá návsi odstraněním prodejny, přesunem obchodu a hospody do rodného domu M. Žďárského a přeměnou obecního domu na tělocvičnu. Cílem je propojit historické jádro s moderními funkcemi a vytvořit multifunkční veřejný prostor.

The former school building in Kožichovice, founded in 1789, has undergone multiple transformations and now awaits adaptation. The urban design proposal opens up the village square by removing the existing shop, relocating the store and pub into M. Žďárský’s birthplace, and converting the former municipal building into a gymnasium . The goal is to link the historic core with modern functions and create a multifunctional public space.
Urban "Skiluaf technician" Kožichovice
Keywords: Tělocvična Náves Centrum Kožichovice Matyáš Žďárský; Gymnasium Village square Centre Kozichovice Matyas Zdarsky